2011
DOI: 10.1159/000330117
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of <i>Platycodon grandiflorum</i> against Chronic Ethanol-Induced Oxidative Stress in C57BL/6 Mice

Abstract: Aims: This study was carried out to evaluate the hepatoprotective effect of Platycodon grandiflorum (PG) in ethanol (EtOH)-induced liver damage. Methods and Results: PG treatment (both the total extract and saponin fraction) significantly blocked EtOH-induced oxidative stress through the preservation of activities of antioxidant enzymes in HepG2 cells. Furthermore, while the administration of EtOH to C57BL/6 mice for 6 weeks induced liver damage, along with a significant increase in plasma glutamic oxalacetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Previous studies indicate that Platycodi Radix (PR), the root of Platycodon grandiflorum , displays beneficial actions against alcohol consumption‐induced hepatotoxicity (Khanal, Choi, Hwang, Chung, & Jeong, ; Noh et al, ). Platycodi Radix treatment decreased elevated AST and P450 2E1 induced by alcohol.…”
Section: Natural Compounds Beneficial For Ald Treatmentmentioning
confidence: 99%
“…Previous studies indicate that Platycodi Radix (PR), the root of Platycodon grandiflorum , displays beneficial actions against alcohol consumption‐induced hepatotoxicity (Khanal, Choi, Hwang, Chung, & Jeong, ; Noh et al, ). Platycodi Radix treatment decreased elevated AST and P450 2E1 induced by alcohol.…”
Section: Natural Compounds Beneficial For Ald Treatmentmentioning
confidence: 99%
“…In clinical practice of oriental medicine, it is often used in combination with basic herbal medicines for detoxification in the treatment of upper respiratory infection, acute and chronic bronchitis [4]. Recently, it has shown the novel pharmacological potentials for treating metabolic diseases, such as hyperlipidemia and diabetes [58]. It has shown that antiobesity and antihypolipidemic effects of platycodin saponins in animal models are due to the inhibition of intestinal absorption of dietary fat [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…It has shown that antiobesity and antihypolipidemic effects of platycodin saponins in animal models are due to the inhibition of intestinal absorption of dietary fat [5, 6]. It showed not only the protective effects on fatty liver via suppression of pancreatic lipase activity [8], as well as acceleration of energy expenditure; but also the hepatoprotective effects on EtOH-induced hepatotoxicity in animal models [810]. However, the mechanism by which Platycodi radix helps to respond in obesity and insulin resistance still remains to be elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Jiegeng is potentially useful as a therapeutically potent natural ingredient for the prevention of chronic alcohol-induced oxidative stress and liver damage [10]. Six triterpenoid saponins have been identified as active components exerting anti-HCV (Hepatitis C virus) activity [11].…”
Section: Hepatoprotective Activitiesmentioning
confidence: 99%